Concept of Educational Interaction in Education: In Sociological Perspective - Ahmad Subakir (Didaktika Religia, 2017)
This article describes the concept of educational interaction in education in a sociological perspective. Sociology has a point of view, certain methods and arrangements. It can be clearly stated that the object of sociology is the study of people in groups, by looking at the nature of society, culture and individuals scientifically. The sociology of education in particular can be interpreted as sociology applied to solve fundamental educational problems that focus on the investigation of the interdependent areas between sociology and the science of education. Educational interaction can be interpreted as a relation activity of various educational elements, educators, administrative staff, and students. The point of interaction in general is a reciprocal relationship among individuals that occur in the community. Educational interaction can only be created if an educator meets the competence and professionalism in the learning process and understands the background of students. An educator plays an important role in creating educational interaction in school. Educational interaction is seen in the implementation of the learning process or the learning stages of an educator. Educational interactions between educators and students are expected to be achieved optimally if there is an awareness of educators that the noble task in teaching and educating students are comprehensive. An educator will be happy and have satisfaction if his or her students succeed.